An examination of large-scale electronic health records implementation in Primary Healthcare Centers in Saudi Arabia: a qualitative study - Haitham A. Alzghaibi (Frontiers in Public Health, 2023)
IntroductionDigital transformation has become a buzzword in almost every industry in the twenti first century. Healthcare is not an exception. In the healthcare industry, digital transformation includes the utilization of electronic health records (EHRs), telemedicine, health information exchange, mobile health, and other interactive platforms. The importance of digital transformation in healthcare cannot be overemphasized as it has proven to be critical in improving patient outcomes, making healthcare delivery more efficient, and reducing costs. The positive impact of electronic health records was noticed almost immediately in the field of primary healthcare. It has been suggested that implementing electronic health records will enhance the accessibility and the process of distribution of health records between authorized users. As part of Saudi vision 2030, all healthcare organizations in Saudi Arabia are going to shift to digital transformation.MethodsThis study follows a qualitative, semi-structure, face-to-face interview approach. The collected data were analyzed using NVivo V10 software. Inductive thematic analysis approach was used to analyse the collected data from the interviews.ResultSeventeen project team members, from different positions and backgrounds were purposively chosen to be interviewed. Three main themes and 38 codes were generated from the analysis of transcripts. The informants describe the implementation of electronic health records in the PHCs based on two different experiences. The participants reported that a previous attempt failed due to inappropriate infrastructure, lack of technical support, and low level of user acceptance. Therefore, the policymakers adopted several steps to increase the level of success and avoid failure causes. They initially established well-defined requests for proposals followed by continuous commendation among the project team and conducted a consultation on multiple levels (country level; organizational level and individual level).ConclusionThis study concluded that the main causes that lead to the failure of the large-scale project were lack of connectivity, lack of technical support, and staff changes, particularly those who occupied high-level positions in the Saudi ministry of Health. The success rate of EHRs implementation can be directly impacted by the size of the project. Large-scale projects are complicated and may be subject to numerous challenges compared with small projects. Significant factors such as training, support, legal issues, and organizational workflow and redesign were a concern of the project team during the pre-implementation phase. In addition, other factors related to technology and end-users were included in the EHRs implementation plan.